Do Interactive Voice Response (IVR) and intra-household and intergenerational deliberation enhance farmers’ irrigation responses in wheat? Field experiments from Nepal - Koirala, Pankaj; Mponela, Powell; Khadka, Lokendra; Kafle, Sagar; Gairhe, Samaya; Krupnik, Timothy Joseph; Lopez-Ridaura, Santiago (CIMMYT, 2025)
Limited adoption of technologies by farmers has been considered one of the barriers for both yield losses minimization and yield improvements. Literature increasingly identifies communicative mechanisms, such as Interactive Voice Response (IVR), to tackle those barriers across different contexts, especially in Africa. However, little is known about its effectiveness on crops’ various yield attributes. To this end, we institute randomized control field experiments among 813 HHs with three treatments: (1) No IVR and No deliberation (base/control group treatment, T1) (2) IVR and No deliberation (T2), and (3) IVR & deliberation (T3) to test how IVR (i.e., recorded agricultural advisories) and/or intra-household deliberation enhances HH’s irrigation responses, along with taking several other sociodemographic variables. In basic treatment, HHs make their irrigation decisions, but they neither distributed IVR nor asked to deliberate. In T1 treatment, recorded IVR-based messages are disseminated directly to the HH through Reengage via mobile phone without the involvement of extension agents or experimenters in message delivery, HHs are additionally asked for intra-household deliberation in T3 after they receive IVR and make irrigation-related decisions. Descriptive analysis from non-parametric tests shows significant differences between treatment pairs, especially district-level analysis indicates IVR’s effectiveness on farmers’ irrigation responses. Regression analysis reveals that farmers with IVR messages increase irrigation events by additional 15.2 percent points while intra-household deliberation provided with IVR message further increase irrigation events by 9.8 percent additional effect, leading to a total of 25 percent. Results also indicate that young farmers (i.e., GenZ, 18 ≥ age < 29 years) irrigate 25.2 percent less irrigation compared to adult farmers (i.e., Millennial & BB, age > 45 years) irrespective of the treatment groups they belong to. The findings demostrate that technology driven advisory services can improve irrigation practices, highlighting the role of intra-household deliberation in reinforcing information uptake. However, the effectiveness of IVR messaging was not uniform across regions. While some rural regions (i.e., Bardiya and Kailali) showed stronger responses to IVR compared to urban (i.e., Chitwan) regions, intra-household deliberation consistently played a positive role, suggesting that fostering family discussions may be key to improving decision-making regardless of regional differences in Nepal and potentially be scaled up in Nepal and with the similar contexts.